2016
DOI: 10.1039/c5en00149h
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in halloysite nanotube derived composites for water treatment

Abstract: Halloysite nanotubes (HNTs) are naturally occurring clay mineral with nanotubular structures and have found increasing potential applications in industrial fields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
74
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(74 citation statements)
references
References 106 publications
0
74
0
Order By: Relevance
“…They are characterized by high mechanical strength and modulus, and due to their hollow nanostructure they are widely used for loading and controlled release of functional compounds (Makaremi et al, 2017;Yang et al, 2016;Huang et al, 2016;Saif and Asif, 2015;Lvov et al, 2016a). HNTs are used in, e.g., self-healing anticorrosive coatings (Wei et al, 2015), hydrogen production and storage (Sahiner and Sengel, 2017;Jin et al, 2017), pharmaceutical excipients (Hanif et al, 2016;Lvov et al, 2016b;Yendluri et al, 2017), biomedical applications Bonifacio et al, 2017), cosmetics (Saif and Asif, 2015), active food packaging materials (Shemesh et al, 2016;Tas et al, 2017;Krepker et al, 2017), water treatment (Yu et al, 2016), and for improvement the mechanical properties and thermal stability of polymer composites (Liu et al, 2014). Globally, HNTs annual production is over 50,000 metric tonnes (Lvov et al, 2008), which is similar to that of carbon fibers (40,000 t/y; Gutiérrez and Bono, 2013), and approximately 10 times higher than the production of carbon nanotubes which is only ca.…”
Section: Introductionmentioning
confidence: 99%
“…They are characterized by high mechanical strength and modulus, and due to their hollow nanostructure they are widely used for loading and controlled release of functional compounds (Makaremi et al, 2017;Yang et al, 2016;Huang et al, 2016;Saif and Asif, 2015;Lvov et al, 2016a). HNTs are used in, e.g., self-healing anticorrosive coatings (Wei et al, 2015), hydrogen production and storage (Sahiner and Sengel, 2017;Jin et al, 2017), pharmaceutical excipients (Hanif et al, 2016;Lvov et al, 2016b;Yendluri et al, 2017), biomedical applications Bonifacio et al, 2017), cosmetics (Saif and Asif, 2015), active food packaging materials (Shemesh et al, 2016;Tas et al, 2017;Krepker et al, 2017), water treatment (Yu et al, 2016), and for improvement the mechanical properties and thermal stability of polymer composites (Liu et al, 2014). Globally, HNTs annual production is over 50,000 metric tonnes (Lvov et al, 2008), which is similar to that of carbon fibers (40,000 t/y; Gutiérrez and Bono, 2013), and approximately 10 times higher than the production of carbon nanotubes which is only ca.…”
Section: Introductionmentioning
confidence: 99%
“…However, the dye rejection ratio for M3 still remained high with a value of 88.1% after adding β‐CD‐HNT additives. The explanations were as follows: on one hand, many reports demonstrated that HNTs emerged negative charge at different pH value . As a result, blending β‐CD‐HNTs could also make PVDF membrane surface having negative charge, which had an electrostatic repulsion with negative dyes .…”
Section: Resultsmentioning
confidence: 99%
“…As a result, blending β‐CD‐HNTs could also make PVDF membrane surface having negative charge, which had an electrostatic repulsion with negative dyes . On the other hand, both β‐CD and HNTs have been used as adsorbents for rapid removal of organic pollutants from water due to their high‐surface‐area and abundant hydroxyl groups . They could have an adsorption reaction with dye molecules, which were not rejected by surface pores of the membrane.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surface modification of the nanotubes, increasing the internal cavity as well as the loading them with various functional compounds can contribute to the change in the properties of the resulting polymer matrix ( Figure ).…”
Section: Modifications Of Nanotubes For the Modulation Of Tissue Engimentioning
confidence: 99%